Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsomega.8b01455
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Case of an Intramolecular Hydrogen Bond Network Forming Four- and Five-Membered Rings in d-Glucose

Abstract: The conformational behavior of cyclic monosaccharides has been widely studied over the past years, but there is no general agreement about which effects are in fact responsible for the observed conformational preferences. A recent microwave spectroscopy study determined the conformational equilibrium of d -glucose in the gas phase with a preference for a counterclockwise arrangement of the hydroxyl groups. Nevertheless, the effects that control this orientation are still uncertain becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It has been reported that the interaction between the hydroxyl groups at C-4 and C-6 in the TG conformation involves unfavorable stereochemistry, 4,44 and steric repulsion has been clearly confirmed using quantum theory. 57 Although further experimental and theoretical studies are necessary, it can be suggested that steric repulsions in addition to the hydration around the hydroxyl group at C-6 affect the structural stabilization of rotamers or rotamerization.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the interaction between the hydroxyl groups at C-4 and C-6 in the TG conformation involves unfavorable stereochemistry, 4,44 and steric repulsion has been clearly confirmed using quantum theory. 57 Although further experimental and theoretical studies are necessary, it can be suggested that steric repulsions in addition to the hydration around the hydroxyl group at C-6 affect the structural stabilization of rotamers or rotamerization.…”
Section: Resultsmentioning
confidence: 99%
“…However, cooperativity between O─H … OH hydrogen bonds in the 1,2‐diol and 1,3‐diol motifs of pyranoses is irregular and not necessarily reciprocal 45, 46 . Klein claims that there is negative cooperativity in glucopyranose, 47 and other authors consider that the driving forces for conformational preferences are steric effects, electrostatic repulsion, and hyperconjugation 48, 49 . The idea of cooperativity involving 1,2‐diol motifs raises the question of hydrogen bonding in such systems: From a topological viewpoint, because there is no bond critical point (BCP), there is no bond 50–58 (and even the idea that a BCP indicates a bond has been discredited—see below).…”
Section: Introductionmentioning
confidence: 99%
“…Among the stereoconformational aspects controlling the molecular arrangements observed in carbohydrates, the anomeric, exoanomeric, and gauche effects are the most prominent . Not by chance, the interpretation of the anomeric effects and other associated stereoelectronic effects in six-membered saturated heterocycles has been extensively documented. , …”
Section: Resultsmentioning
confidence: 99%